Density and infrared band strength of interstellar carbon monoxide (CO) ice analogues. Issue 4 (29th October 2022) - González Díaz, C; Carrascosa, H; Muñoz Caro, G M; Satorre, M Á; Chen, Y-J
ABSTRACT: The motivation to study experimentally CO ice under mimicked interstellar conditions is supported by the large CO gas abundances and ubiquitous presence of CO in icy grain mantles. Upon irradiation in its pure ice form, this highly stable species presents a limited ion and photon-induced chemistry, and an efficient non-thermal desorption. Using infrared spectroscopy, single laser interference, and quadrupole mass spectrometry during CO ice deposition, the CO ice density was estimated as a function of deposition temperature. Only minor variations in the density were found. The proposed methodology can be used to obtain the density of other ice components at various deposition temperatures provided that this value of the density is known for one of these temperatures, which is typically the temperature corresponding to the crystalline form. The apparent tendency of the CO ice density to decrease at deposition temperatures below 14 K is in line with recently published colorimetric measurements. This work allowed us to revisit the value of the infrared band strength needed for calculation of the CO ice column density in infrared observations, 8.7 × 10 −18  cm molecule −1 at 20 K deposition temperature.